Students’ Perception toward Independent Listening Using TED Talks - Nenti, Nitra Windhachaya; Perdhani, Widya Caterine (Journal of English Language and Education, 2024)
The utilization of video content offers visually captivating elements that captivate pupils, while its accessibility across several platforms renders it very adaptable. Various videos, including those from TED Talks, can be used for English language acquisition. The research focused on the perspectives from learners on using TED Talk videos for the purpose of self-directed listening. The study utilizes a quantitative survey design as its approach. The researcher administered an online questionnaire consisting of close-ended questions to a sample of 12th grade students at SMAN 10 Malang. The findings show TED conference videos had a beneficial effect on enhancing the listening abilities of learners. Most learners have the capacity to improve their vocabulary and their ability to understand several diverse accents. Moreover, participating in individual listening can equip students with a foundational understanding of the complexities.